An improved design procedure for LCC resonant filter of dimmable electronic ballasts for fluorescent lamps, based on lamp model - Wakabayashi, Fabio Toshiaki [UNESP]; Canesin, Carlos Alberto [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2005)
This paper presents an improved design methodology for the determination of the parameters used in the classical series-resonant parallel-loaded (SRPL) filter employed in the switching frequency controlled dimmable electronic ballasts. According to the analysis developed in this paper, it is possible to evaluate some important characteristics of the resonant filter during the dimming operation, such as: range of switching frequency, phase shift, and rms value of the current drained by the resonant filter + fluorescent lamp set. Experimental results are presented in order to validate the analyses developed in this paper. © 2005 IEEE.
Keywords: Dimmable electronic ballasts; Half-bridge inverter; Resonant filter + fluorescent lamp set; Series-resonant parallel-loaded (SRPL) filter; Dimming (lamps); Electric filters; Equivalent circuits; Fluorescent lamps; Phase shift; Resonant filter; Series resonant parallel loaded filter; Ballasts (lamp)